The Mitochondrion as Potential Interface in Early-Life Stress Brain Programming - Hoffmann, Anke; Spengler, Dietmar (Frontiers in Behavioral Neuroscience, 2018)
Mitochondria play a central role in cellular energy-generating processes and are master regulators of cell life. They provide the energy necessary to reinstate and sustain homeostasis in response to stress, and to launch energy intensive adaptation programs to ensure an organism’s survival and future well-being. By this means, mitochondria are particularly apt to mediate brain programming by early-life stress (ELS) and to serve at the same time as subcellular substrate in the programming process. With a focus on mitochondria’s integrated role in metabolism, steroidogenesis and oxidative stress, we review current findings on altered mitochondrial function in the brain, the placenta and peripheral blood cells following ELS-dependent programming in rodents and recent insights from humans exposed to early life adversity (ELA). Concluding, we propose a role of the mitochondrion as subcellular intersection point connecting ELS, brain programming and mental well-being, and a role as a potential site for therapeutic interventions in individuals exposed to severe ELS.